A Case of Ischemic Stroke With Congenital Protein C Deficiency and Carotid Web Successfully Treated by Anticoagulant and Carotid Stenting - Watanabe, Sadayoshi; Matsumoto, Shoji; Nakahara, Ichiro; Ishii, Akira; Hatano, Taketo; Mori, Minako; Morishita, Eriko; Nagata, Izumi (Frontiers in Neurology, 2020)
Objective: A rare case of thromboembolic cerebral infarction due to carotid web in a patient with congenital protein C deficiency is reported. Case presentation: A patient in her 40’s with left-side hemiparesis was transferred to our hospital under continuous intravenous injection of heparin. Magnetic resonance angiography demonstrated occlusion of the right middle cerebral artery (MCA). Conventional angiography revealed recanalization of the right MCA and a carotid web at the origin of the right internal carotid artery. Ultrasound scan of the carotid artery on the 19th day revealed thrombus formation on the distal portion of the carotid web. We performed carotid artery stenting to prevent thrombus formation by suppressing the carotid web to the vessel wall and by regulating the turbulent flow. The patient had no recurrence of stroke under-anticoagulation with warfarin during the 2-year follow-up period. Conclusion: To our knowledge, this is the first report in which an immediate thrombus formation on the carotid web was observed in a patient with congenital protein C deficiency. In a case of acute ischemic stroke with carotid web, especially when congenital coagulopathy such as protein C deficiency is suspected, careful follow-up with ultrasound imaging should be performed.